Tradisi Perhitungan Weton Jawa Sebagai Pandangan Hidup Dalam Pernikahan Keluarga Jawa Di Desa Sidodadi Gorontalo - Jasmine Shafira Prameswari; Maria Heny Pratiknjo; Titiek Mulianti (Universitas Lambung Mangkurat, 2026)
The tradition of calculating weton in marriage is still upheld by the Javanese community in Sidodadi Village, Boliyohuto Subdistrict, Gorontalo Regency, passed down from generation to generation without significant changes in its implementation. This study aims to understand the existence and meaning of the weton tradition as a worldview in marriage, as well as the dynamics of its preservation across generations. The research employs a qualitative method with a descriptive-analytical approach, using in-depth interviews and participatory observation. The findings reveal that the older generation continues to strongly adhere to the weton tradition, as it is believed to bring blessings and household harmony. Meanwhile, the younger generation tends to be more flexible in its application, prioritizing emotional and financial readiness. The role of traditional leaders in preserving this tradition is highly significant, especially in providing proper understanding to the younger generation. The weton tradition serves not only as a spiritual guide but also as a symbol of Javanese identity in transmigrant areas. Despite differing perceptions among the youth, the tradition is maintained as a form of respect for ancestral values. The study concludes that the adaptation of the weton tradition within the context of modern life remains viable, provided that there is a compromise between traditional values and the practical needs of society.